Avaliação da qualidade dos serviços na biblioteca da UFERSA Campus Angicos-RN: aplicação do modelo de Kano - Medeiros, Moisés Rocha Martins de (Universidade Federal Rural do Semi-Árido, 2019)
With the increasing number of consumers who became each day more exacting and aware of yours right, it is of fundamental importance that companies seek to meet the needs and expectations of the costumers, seeking satisfaction. In the context of public service, this is important because ethical and social quality services have become even more important when targeted at this type of service, this is happening because the provision of the service performed by the public service keeps the focus on the very existence of the service, leaving the quality in the background. This article aims to evaluate the quality of service provided by the library of the campus UFERSA Angicos-RN through the application of Kano Model, aiming to identify which quality attributes are responsible for generating more customer satisfaction. To achieve this objective, an exploratory study was used as a research method, with a survey conducted with students who use library services and using quantitative data analysis (descriptive statistics, Cronbach’s alpha and coefficients of satisfaction). To collect the data to be analyzed, an online questionnaire was made available to students who are studying at UFERSA and have already used this answering service. Through the results obtained in the data collection, it was possible to identification that all the answers the unidimensional attribute was predominant for the participants who frequents the library, this is very important as the evaluation of university libraries has played an important role in the evaluation of higher education institutions and undergraduate courses. It was possible to identify the main requirements that influences the satisfaction of campus library users applications of the Kano model, with the concept of completion Kano is an excellent alternative to be used in measuring the degree of satisfaction of a particular type of public service.
Artigo
Keywords: Biblioteca universitária; Qualidade em serviços; Modelo Kano; University library; Quality in services; Kano model; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA